Social and Cultural Situation in the Context of Linguistic Policy in Ukraine 50-60th of the XXth Century - Tievikova, Olga; Doroshenko, Svitlana; Lysenko, Alla; Naradko, Andrii (International Journal of Engineering and Technology, 2018)
The article considers the peculiarities of the social and cultural linguistic situation in Ukraine in 1950s-1960s. A special attention is paid to the fact that there was a Ukrainian-Russian way of communication that was a result of the active and purposeful implementing of the Russian language into all spheres of social life of soviet Ukrainians. The authors prove that the purposeful russification, damaging and discreditation of the Ukrainian language slowed down the development of Ukrainian national culture. It has become a threat for consolidation and development of Ukrainian nation. In the result, nowadays we deal with the linguistic incompetence and the low level of realizing the national self-identity of Ukrainians who started to depend on historical realias. The study of the development of the Ukrainian language at various stages of its formation is very important. It helps to understand the causes and find ways to solve many modern language problems. Thus, an this article is an actual and important scientific research. Authors study such important issues as the linguistic incompetence of Ukrainians, the existence of bilingualism, the priority of the Russian language and the influence of Russian culture, the low level of national self-awareness, national self-identity, and others. the authors made a thorough analysis of the peculiarities of the linguistic situation in Ukraine in the 1950s and 1960s, studied the content, factors and implications of the linguistic policy of Soviet power in Ukraine, outlined the prospects for future research in this field.Â